Are Consumers in Developing Countries Willing to Pay for Food Safety Attributes? Evidence from Klang Valley, Malaysia - Ramli, Nurul Nadia; Joya, Khalid; Shamsudin, Mad Nasir; Kamarulzaman, Nitty Hirawaty (AGRARIS: Journal of Agribusiness and Rural Development Research, 2026)
Rising incomes and urbanization have increased consumer demand for safer food. In Malaysia, concerns over pesticide use and international produce recalls have further emphasised the importance of enhancing food safety attributes to meet changing consumer preferences. Therefore, this study attempts to determine consumers’ willingness to pay for safety attributes of carrots. The survey was conducted in the Klang Valley, with 490 respondents successfully responding to the questionnaires. The study employed the discrete choice experiment (DCE), and the findings revealed that consumers were willing to pay more for carrots food safety attributes. The study also found that other factors that can influence the willingness to pay for safety attributes of carrots include income, education level and age. These findings underscore the importance of complying with safety standards for fresh produce since consumers are willing to pay more for safety attributes of carrot.